Bahan-bahan tentang Islam dalam koleksi John Bastin - Denisova, T.A. (Dept. of Islamic History and Civilization, Academy of Islamic Studies, University of Malaya, Kuala Lumpur, 2009)

(untitled)
John Bastin’s compilations contain a group of books about Malay’s history and culture. His collections consist of more than 3,000 books about history, archeology, economy, cultural, geography, and so on. From all his collections, only 13 books are related to Islam. That books are about the history of Islam in Malay archipelago, history of Islamic preaching, hajj and rituals in Islam, Islamic movement on 20th century and present, etc. Analysis to the John Bastin’s collection as a historiography source unity, is significant in knowledge tradition research and historiography in Malay Archipelago to clarify and deny prejudice as well as decrease misunderstanding regarding of elements in Malay Civilization and Malay manuscripts, to develop international dialogue and to find general language between Muslims and West in the new world.